Area of institute’s activities for students’ orientation on agricultural industry professions - Irina G. Kondaurova; Larisa A. Filipovich (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Urgency of the article was due to the fact that within a market economy, socio- economy situation in country is changing, and thus labor-market is changing to, this is why it’s necessary to pay more attention to organization of targeted vocational guidance work in all stages of education process, starting from school education and ending with alumnus of vocational training institution. Vocational guidance is considered as complex of educational and learning impacts on personality; allow self-dependence for choosing of profession; allow realizing ability and inclination of personality. Modern conditions are required from agricultural institutes establishing new policy in agricultural sphere. Now we have a task for establishing for all institutions union spatial strategy in professional agricultural education; objectivation of adjustment mechanism of educational institution for new social and demographic situation that is emerging in the region especially in Kemerovo region. In the article were analyzed different ways and forms of events organization, developed by Kemerovo State Agricultural Institute, which are directed to make students chose agricultural industry profession. By analyzing institution activity in given field, conclusion was made, that it is necessary to improve vocational guidance work in institutes by using new methods and forms of work, which are actual for modern requests of schools and secondary-vocational educational institution and can exactly perform coordination function in vocational guidance work, to provide, self-dependence, realization of profession choice and continuity for given process.